(3GdYbhO GdUZjQI (B:s (3YbO GdJCejf (B/s - (3WdHI, CfhQs ((3GdEScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2004)
(3YbO GdJCejf(B- (3CMcGe YbO GdJCejf(B- (3GdOYGhj GdfGTFI Yf YbO GdJCejf(B- (3GdJCejf aj Gdfbd GdHQj(B- (3GdJCejf GdLeGYj(B- (3JbGOe GdOYGhj GdfGTFI Yf YbO GdJCejf(B- (3GdhbGFY GdJj dG JNVY ddJbGOe GdKdGKj(B-(3BKGQ YbO GdJCejfs
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdYbhOs